Knowledge Mangement System sebagai Dasar Pengembangan Sistem Informasi Kinerja Dosen - Terttiaavini Terttiaavini; Fakhry Zamzam; Muhammad Ramadhan; Tedy Setiawan Saputra (Jurnal Informatika Global)
In the current digitalization era, the application of knowledge management systems can improve the performance of information systems for the better. The knowledge management system is very important to be implemented in higher education. Having different abilities in implementing the tri dharma of higher education, therefore it is necessary to share knowledge to increase the career advancement of lecturers. The development of a lecturer performance information system based on a knowledge management system is an information system used to carry out community service activities. This system can also generate information on the achievement of targets every semester. The target achieved will be used for determining rewards and punishments. The method used for software development is a waterfall. The classical method is still often used because the stages are simpler and easier to implement. Lecturer performance information systems can help programs and supervise, run and improve the performance of lecturers at Universitas IGM